Electropharmacological effects of intracellular Ca2+ handling modulator caldaret on the heart assessed in the halothane-anesthetized dogs - Atsushi Sugiyama; Mihoko Hagiwara-Nagasawa; Ryuichi Kambayashi; Ai Goto; Koki Chiba; Kentaro Ando; Atsuhiko T. Naito; Hiroko Izumi-Nakaseko (Elsevier, 2019)
We analyzed how the enhancement of net sarcoplasmic reticulum (SR) Ca2+ uptake may affect cardiac electrophysiological properties in vivo by using caldaret which can decrease SR diastolic Ca2+ leak, enhance SR Ca2+ reuptake and inhibit reverse-mode Na+/Ca2+ exchanger. Caldaret in doses of 0.5, 5 and 50 μg/kg was intravenously administered over 10 min to the halothane-anesthetized beagle dogs (n = 5), attaining pharmacologically active plasma concentration. The low and middle doses of caldaret increased the ventricular contraction, which could be explained by its on-target pharmacological activities. The high dose enhanced the sinus automaticity followed by its suppression in addition to the increase of the total peripheral resistance, which may be unfavorable for treating diastolic heart failure. The low and middle doses enhanced the atrioventricular conduction, which may have some potential for predisposing the atria to the onset of atrial fibrillation via an induction of mitral and/or tricuspid regurgitation. The middle and high doses of caldaret prolonged the ventricular effective refractory period without altering the intraventricular conduction or repolarization period, which may prevent the onset of ventricular arrhythmias. Thus, modulation of intracellular Ca2+ handling by caldaret can induce not only inotropic effect, but also various electrophysiological actions on the in situ heart. Keywords: Caldaret, Ryanodine receptor, Sarco/endoplasmic reticulum Ca2+-ATPase, Reverse-mode Na+/Ca2+ exchanger